ANALISIS INDEKS KEBAHAGIAAN KEPALA SEKOLAH DAN GURU DALAM KEGIATAN BIMBINGAN TEKNIS PROGRAM SEKOLAH PENGGERAK - Rasidi Rasidi; Robiul Fitri Mashitoh (Jendela Inovasi Daerah, 2022)
“Sekolah Penggerak” is a policy of the Ministry of Education, Culture, Research, and Technology, since 2021. The program is an effort to realize Indonesia's education vision in realizing "A Sovereign, Independent, and Personalized Advanced Indonesia through the Creation of Pelajar Pancasila." Development of student learning outcomes holistically which includes competence (literacy and numeracy) and character, with superior human resources (principals and teachers). The purpose of this study is to reveal the psychological side by discussing the happiness index of principals and teachers in increasing happiness in the technical guidance of “Sekolah Penggerak”. The method used is the mix method. The data begins with quantitative research to see the condition of the happiness index descriptively, then traces a qualitative approach and looks for the root of the problem and the solution chosen. Furthermore, an analysis is carried out to find solution recommendations to solve the problems of happiness experienced by teachers and principals. The results showed that the happiness index in following the technical guidance showed an average of 80 %. The influencing factors are internal and external factors. The internal factors are 1) the interest of the technical guidance participants to the adaptation of the independent curriculum, 2) the teacher's self-concept, 3) self-management. The external factors are 1) the living environment, 2) the ability of the technical guidance facilitator, 2) the support of colleagues at school.